Pertanggungjawaban Pidana Bagi Pelaku Penyelundupan Satwa Liar Yang Dilindungi - Ridho Afrizal Abd Rohim; Ifahda Pratama Hapsari; Dodi Jaya Wardana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The legal regulation of endangered animal smuggling in Indonesian positive law is legal protection which aims to prevent the threat of extinction and the development of endangered species whose existence is threatened due to conflict and illegal hunting. This research uses normative legal research methods with a statutory approach, conceptual approach and case approach. Animal smuggling is not mentioned explicitly in Law No. 5 of 1990 concerning Conservation of Natural Resources and Ecosystems. However, this law regulates the prohibition on catching, injuring, killing, keeping, possessing, caring for, transporting and trading protected animals alive, or removing protected animals from one place in Indonesia to another place inside or outside Indonesia. This is stated in Article 21 paragraph (2) of Law No. 5 of 1990. Criminal sanctions for criminal acts of smuggling endangered species based on positive law in Indonesia are contained in Article 40 paragraphs (2) and (4) of Law Number 5 of 1990 Concerning Conservation of Living Natural Resources and their Ecosystems, in the form of imprisonment and fines, imprisonment and fines, plus confiscation of all objects obtained and all tools or objects used to commit criminal acts, with a statement that they are confiscated to the state.